Community-Partnered Collaboration to Build an Integrated Palliative Care Clinic: The View From Urology. (March 2016) - Bergman, Jonathan; Ballon-Landa, Eric; Lorenz, Karl A.; Saucedo, Josemanuel; Saigal, Christopher S.; Bennett, Carol J.; Litwin, Mark S.
Background: We partnered with patients, families, and palliative care clinicians to develop an integrated urology–palliative care clinic for patients with metastatic cancer. We assessed clinician satisfaction with a multidisciplinary palliative care clinic model. Methods: We conducted semi-structured interviews with 18 clinicians who practice in our integrated clinic. We analyzed transcripts using a multistage, cutting-and-sorting technique in an inductive approach based on grounded theory analysis. Finally, we administered a validated physician job satisfaction survey. Results: Clinicians found that referring a patient to palliative care in the urology clinic was feasible and appropriate. Patients were receptive to supportive care, and clinicians perceived that quality of care improved following the intervention. Conclusion: An integrated, patient-centered model for individuals with advanced urologic malignancies is feasible and well received by practitioners.